Inflammation and Nutritional Status Mediated the Increased of Risk of Atrial Fibrillation Recurrence Associated with eGFRdiff Post-Ablation - Huang W; Liu H; Luo Y; Xiong S; Suo S; Zhang Z; Shang L; Sun H (Journal of Inflammation Research)
Wenchao Huang,1 Hanxiong Liu,1 Yan Luo,1 Shiqiang Xiong,1 Shuwei Suo,1 Zhen Zhang,1 Luxiang Shang,2,3 Huaxin Sun1 1Department of Cardiology, The Third People’s Hospital of Chengdu, Chengdu, Sichuan, 610031, People’s Republic of China; 2Department of Cardiology, The First Affiliated Hospital of Shandong First Medical University and Shandong Provincial Qianfoshan Hospital, Shandong Medicine and Health Key Laboratory of Cardiac Electrophysiology and Arrhythmia, Jinan, Shandong, 250014, People’s Republic of China; 3Medical Science and Technology Innovation Center, Shandong First Medical University & Shandong Academy of Medical Sciences, Jinan, Shandong, 250117, People’s Republic of ChinaCorrespondence: Huaxin Sun, Department of Cardiology, The Third People’s Hospital of Chengdu, Chengdu Cardiovascular Disease Research Institute, 82 Qinglong St, Chengdu, Sichuan, People’s Republic of China, Email gracekelly1994@163.com Luxiang Shang, Medical Science and Technology Innovation Center, Shandong First Medical University & Shandong Academy of Medical Sciences, Jinan, Shandong, 250117, People’s Republic of China, Email shangluxiang@163.comBackground: Serum creatinine and cystatin C levels are influenced by different non-renal factors. The difference between the estimated glomerular filtration rates (eGFRdiff) based on these two markers helps assess cardiovascular risk factors unrelated to kidney function. However, its impact on post-ablation atrial fibrillation (AF) recurrence remains unknown.Methods: From July 2017 to February 2023, we prospectively observed 989 consecutive AF patients who underwent radiofrequency ablation. The association between eGFRdiff and post-ablation AF recurrence was analyzed using Kaplan-Meier methods, adjusted Cox regression analysis, and restricted cubic spline (RCS) analysis.Results: During a median follow-up period of 29 months, 326 cases of AF recurrence were detected. Participants were divided into three groups based on eGFRdiff: high (≥ − 9.22), medium (− 20.98 to − 9.22), and low (≤ − 20.98). Multivariable Cox proportional hazards models revealed that, compared to the medium eGFRdiff group, individuals in the low eGFRdiff group (hazard ratio [HR] 1.46, 95% confidence interval [CI] 1.08– 1.94, p < 0.01) and the high eGFRdiff group (HR 1.69, 95% CI 1.27– 2.27, p < 0.01) had a significantly increased risk of AF recurrence. RCS analysis demonstrated a U-shaped association between eGFRdiff and AF recurrence. Stratified analyses confirmed the robustness of the core findings across subgroups, except for females. Notably, the geriatric nutritional risk index and the derived neutrophil-to-lymphocyte ratio partially mediated the association between eGFRdiff and high AF recurrence by 5.7% and 10.7%, respectively.Conclusion: eGFRdiff is related to individual nutritional and inflammatory statuses and can be used to predict the risk of AF recurrence. (Clinical trial registration number: ChiCTR-OIN-17013021).Plain Language Summary: This study investigated the association between eGFRdiff and AF recurrence after ablation. eGFRdiff is calculated from two different markers in the blood (creatinine and cystatin C), which reflect both kidney health and other body conditions like nutrition and inflammation. We followed 989 patients who had AF and underwent ablation from July 2017 to February 2023. We found that eGFRdiff was much higher or lower, the risk of AF recurrence increased, forming a U-shaped curve. This pattern was consistent in most groups of patients, except for women who showed a different trend. Our findings suggest that both nutritional status and inflammation play roles in AF recurrence, but their impacts differ based on eGFRdiff levels. Poor nutrition was more significant at lower eGFRdiff levels, while inflammation was more crucial at higher levels. Interestingly, inflammation seemed to have a stronger impact on women. These insights emphasize the need to monitor and manage patients’ nutritional and inflammatory status to reduce the risk of AF recurrence, especially considering sex-specific factors. Future larger studies are needed to confirm these results and further refine treatment strategies.Keywords: atrial fibrillation, estimated glomerular filtration rate, cystatin C, creatinine, recurrence